IMPLEMENTATION OF THE INTEGRATED DYNAMIC ARCHIVAL INFORMATION SYSTEM (SRIKANDI) POLICY AT UPT STATE VOCATIONAL HIGH SCHOOL 3 WAJO - Sitti Aminah; Syamsiar; Imran Ismail; Jumrah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to explore the implementation of the Integrated Dynamic Archiving Information System policy at UPT Vocational High School 3 Wajo in improving the administrative process to be more effective, fast and transparent in supporting the learning and administrative activities at school. The method used is a qualitative method. Data were collected through observation, interviews, and documentation. The results of the study indicate that the implementation of the Integrated Dynamic Archiving Information System policy at UPT Sekolah Menengah Kejuruan 3 Wajo has been implemented well so that teachers and staff are greatly assisted in improving the administration and archiving processes in supporting the administration process, teaching and learning activities in the school environment. The Srikandi application is very helpful in managing archives and correspondence electronically. This application can also improve work efficiency and effectiveness and also the UPT SMK Negeri 3 Wajo has provided facilities and infrastructure such as computer/laptop devices with good and adequate specifications, and has tried to further improve the quality of wifi/networks at school. and support users to take part in training to develop application management competencies